Faktor Yang Berhubungan dengan Kejadian Tuberkulosis Paru - Agung Sutriyawan; Nofianti Nofianti; Rd. Halim (Sarana Ilmu Indonesia (salnesia), 2022)
Abstract Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis that has infected nearly one-third of the world's population. The study aimed to analyze the relation of knowledge, nutritional status, and smoking habits to the incidence of tuberculosis. The research used quantitative methods and cross-sectional design. The population was a patient who visits in and is registered in the patient register at Puskesmas Garuda. Samples were taken from as many as 95 subjects. Sampling used simple random sampling techniques. The statistical test used was the chi-square test. Variables that had been shown to be associated with the incidence of tuberculosis are knowledge (p-value =0,018), nutritional status (p-value=0,012), and smoking habits (p-value=0,000), the prevalence of tuberculosis is 41,1%. Risk factors of tuberculosis are knowledge, nutritional status, and smoking freedom. People who are knowledgeable about tuberculosis. It is recommended that health workers are advised to increase preventive and promotive efforts through counseling about the risk factors of tuberculosis events to the public to increase public knowledge in order to reduce the risk of being infected with tuberculosis.